IMPLEMENTATION OF EXTENDED UTAUT 2 IN ANALYZING THE INTENTION AND BEHAVIOR OF LINKEDIN USAGE - Meilinda Meilinda; Stefanus Setyo Wibagso (Jurnal Sistem Informasi dan Sains Teknologi, 2025)
Nowadays, with advancements in digital technology, the internet and social media have dominated daily routines, particularly LinkedIn, which has transformed professional interaction and development. With over 1.15 billion global users by 2025, LinkedIn offers various features for job searching and skill development. However, there is a gap between the number of registered accounts and active users, indicating challenges related to security and privacy. This study applies the Extended UTAUT 2 model in analyzing various factors that shape LinkedIn user intention and behavior. Through data collection from 243 respondents in Indonesia, the results show that Performance Expectancy, Effort Expectancy, Price Value, Hedonic Motivation, Facilitating Conditions, and Privacy Risk have a significant influence on Behavioral Intention and Use Behavior. However, the moderating effect of Experience is not significant. This model provides a deeper understanding of LinkedIn adoption and can serve as a basis for strategies to enhance user engagement.